Wear-resistant nanofiber membrane composite fabric and preparation method thereof
Patent Information
- Application Number
- CN202611027951.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-02
AI Technical Summary
[0004]解决的技术问题:针对上述现有技术中存在的纳米纤维膜涂层洗后水压不稳定,韧性不足、易撕裂,耐磨耐刮性能特别差等问题,本发明提出一种耐磨纳米纤维膜复合面料及其制备方法,通过开发一款耐磨耐刮的浆料,以辊印的方式,使纳米纤维膜材料具有很好的耐磨性能、耐水洗性能,同时又能提升产品的抗渗水性,对透气性影响较小等,同时还要有与热熔胶较好的结合牢度,满足服装日常服用需求
[0025]综上所述,通过对纳米纤维膜表面耐磨辊印处理,在保证原有耐水压性、透湿性等指标的前提下,耐磨耐刮性能得到了巨大的提升,同时透气性损失较小,满足服用需求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional fabric technology, specifically relating to a wear-resistant nanofiber membrane composite fabric and its preparation method. Background Technology
[0002] With increasing attention to health, the market for outdoor functional sports fabrics has grown significantly in recent years, leading to a greater demand for waterproof and breathable fabrics. Traditional waterproof and breathable finishing processes typically involve coatings or laminations, which offer good waterproofing and breathability, but their biggest drawback is poor air permeability. When physical activity increases, the moisture and heat evaporated from the body cannot be effectively dissipated, resulting in a damp and stuffy feeling. The application of nanofiber membranes in clothing effectively solves this problem. Their highly porous microporous structure allows for the rapid and effective removal of moisture and heat, increasing comfort while providing excellent waterproofing, windproofing, and warmth retention.
[0003] Although nanofiber membranes have excellent performance in waterproofing, moisture permeability, and air permeability, they also have their drawbacks due to the characteristics of the material itself and the influence of the processing technology. These drawbacks mainly include unstable water pressure after washing, insufficient toughness, easy tearing, and particularly poor wear and scratch resistance. Summary of the Invention
[0004] Technical problem solved: Addressing the issues of unstable water pressure, insufficient toughness, easy tearing, and particularly poor abrasion and scratch resistance in existing nanofiber membrane coatings, this invention proposes an abrasion-resistant nanofiber membrane composite fabric and its preparation method. By developing an abrasion-resistant and scratch-resistant slurry, and using roller printing, the nanofiber membrane material achieves excellent abrasion resistance and washability, while also improving the product's water resistance and minimizing the impact on breathability. Furthermore, it must have good bonding strength with hot melt adhesive to meet the daily wear requirements of clothing.
[0005] Technical Solution: The first objective of this invention is to provide a wear-resistant nanofiber membrane composite fabric, comprising a fabric base, a nanofiber membrane bonded thereto, and a wear-resistant coating disposed on the surface of the nanofiber membrane. The wear-resistant coating is formed by roller printing and drying of a wear-resistant slurry. The raw materials of the wear-resistant slurry are formulated in the following proportions by weight: 20-40 parts of waterborne polyurethane emulsion, 2-6 parts of modified nano silica, 2-3 parts of thickener FS-20A, 0.5-1.5 parts of dispersant 5040, 1-2 parts of crosslinking agent DF-810, 1-2 parts of wetting agent 8502C, and water to make up to 100 parts.
[0006] Preferably, the dry weight gain of the coating is 4-16 g / m³. 2 .
[0007] Preferably, the base fabric is 70D nylon four-way stretch with a weight of 125 g / m². 2 .
[0008] Preferably, the nanofiber membrane is a highly elastic and breathable nanofiber membrane S2A with a thickness of 15 μm and a basis weight of 9 g / m³. 2 .
[0009] Preferably, the waterborne polyurethane emulsion is waterborne polyurethane FS-781, and the modified nano silica is CY-SP30H.
[0010] The second objective of this invention is to provide a method for preparing the aforementioned wear-resistant nanofiber membrane composite fabric, comprising the following steps:
[0011] Step 1: The fabric base and the nanofiber membrane are laminated together on a laminating machine using hot melt adhesive to obtain the composite fabric;
[0012] Step 2: Prepare abrasion-resistant slurry, wherein the abrasion-resistant slurry comprises an aqueous polyurethane emulsion, modified nano-silica, thickener, dispersant, crosslinking agent, wetting agent, and water;
[0013] Step 3: Apply the abrasion-resistant slurry to the nanofiber membrane surface of the composite fabric using a roller printing method;
[0014] Step 4: Dry the composite fabric with the applied abrasion-resistant slurry to form an abrasion-resistant coating on the surface of the nanofiber membrane.
[0015] Preferably, in step one, the base fabric undergoes a water-repellent treatment before lamination, with a water repellency level ≥ 4. The water-repellent treatment is as follows: 4 wt% of waterproofing agent FD-8 and 0.3 wt% of crosslinking agent 891A are mixed, and water is added to 100 wt%. The fabric is then dried in an oven at 160℃ for 2 minutes after two dips and two rubs.
[0016] Preferably, the hot melt adhesive used in step two is a reactive polyurethane hot melt adhesive, with an application rate of 8-12 g / m³. 2 After lamination, the material is cured at a temperature of 25°C and a humidity of not less than 50% for 2 days.
[0017] Preferably, in step three, the preparation method of the wear-resistant slurry is as follows: First, the dispersant is added to water and dissolved under low-speed stirring at 500 rpm; then, modified nano-silica is slowly added in batches under high-speed shearing at 1200 rpm and dispersed evenly; the dispersed silica mixture is mixed and stirred evenly with the aqueous polyurethane emulsion; then, a wetting agent is added and stirred evenly at low speed at 500 rpm; finally, a thickener is slowly added under continuous low-speed stirring at 500 rpm to adjust to the target viscosity of 2500 cps.
[0018] Preferably, in step four, the drying process is as follows: drying at 150-160℃ for 2 minutes.
[0019] The waterborne polyurethane used in this invention consists of alternating hard and soft segments in its molecular chain. The hard segments are typically generated by the reaction of isocyanates with small-molecule chain extenders and contain a large number of highly polar urethane bonds (-NHCOO-). These polar groups can form strong hydrogen bonds, causing the hard segment regions to aggregate and imparting rigidity, hardness, and strength to the material. The soft segments are typically composed of long-chain polyethers or polyester polyols, with flexible molecular chains that impart elasticity and flexibility to the material. This microphase separation structure allows the hard segments to provide resistance to deformation when the material is subjected to friction, while the soft segments absorb and disperse stress through deformation.
[0020] The basic structural unit of the modified nano-silica (SiO2) used in this invention is [silicon-oxygen tetrahedron (SiO4)]. Silicon (Si) and oxygen (O) atoms are connected by high-energy Si-O covalent bonds, forming an extremely robust and stable three-dimensional network structure. This gives the nano-silica itself extremely high intrinsic hardness, typically reaching 6-7 on the Mohs scale, far exceeding most polymers and organic coatings. When used as a filler embedded in composite materials, it effectively resists ploughing and scratching caused by external friction. The surface of the nano-silica is rich in silanol groups (-SiOH). These hydroxyl groups have high reactivity; on the one hand, they can strongly interact with polar groups in resin matrices such as waterborne polyurethane (WPU) (e.g., C=O, NH in urethane esters) through hydrogen bonding; on the other hand, they can form covalent bonds with the matrix through surface modification (e.g., using silane coupling agents). This strong interfacial bonding is key to wear resistance, ensuring that the nanoparticles are not easily "pulled out" during friction but are firmly anchored in the matrix, becoming effective stress-bearing points.
[0021] The thickener used in this invention can quickly lock in the aqueous phase and impart specific rheological properties, enabling precise control of leveling, penetration, water retention, and ensuring clear contours.
[0022] The dispersant used in this invention is a surfactant that can significantly reduce the surface tension of the dispersion medium, making it easier to penetrate into the gaps of the aggregates and completely wet and encapsulate each nanoparticle.
[0023] The crosslinking agent used in this invention crosslinks the organic matter in the polyurethane emulsion with nano-silica to form a huge network structure in which the molecular chains are fixed, thereby increasing the bonding strength and improving the wear resistance.
[0024] The wetting agent used in this invention can effectively change the surface tension of the nanofiber membrane, allowing the polyurethane adhesive to spread rapidly on the membrane surface and complete the penetration and wetting process.
[0025] In summary, by applying abrasion-resistant roller printing treatment to the surface of the nanofiber membrane, the abrasion and scratch resistance are greatly improved while maintaining the original water pressure resistance and moisture permeability, and the loss of air permeability is minimal, thus meeting the needs of wearers.
[0026] Beneficial effects: This invention mainly addresses the problems of unstable water pressure and poor scratch resistance of nanofiber membranes after washing by using a roller-printed abrasion-resistant paste on the surface of the membrane. The formulation and amount of the abrasion-resistant paste directly affect the performance of relevant indicators, especially wash resistance; therefore, process control is crucial. Verification showed that a printing paste amount of 8-10 g can both improve post-wash water pressure and enhance the scratch resistance of the membrane material.
[0027] The final performance indicators achieved are: hydrostatic pressure ≥80 kPa, water pressure ≥35 kPa after 5 washes, air permeability ≥2.0 mm / s, and moisture permeability ≥6800 g / m³. 2 • 24 hours. Detailed Implementation
[0028] The present invention will be further described below with reference to specific embodiments.
[0029] Unless otherwise specified, the raw materials used in the embodiments of this specification are all from common commercially available products, including:
[0030] The reactive polyurethane hot melt adhesive was purchased from Zhongzhan Technology, and its model is hot melt adhesive FG-3308.
[0031] The waterborne polyurethane emulsion, purchased from Liaoning Hengxing Chemical Co., Ltd., is model FS-781. This waterborne polyurethane molecular chain consists of alternating hard and soft segments. The hard segments are typically generated by the reaction of isocyanates with small-molecule chain extenders, containing a large number of highly polar urethane bonds (-NHCOO-). These polar groups can form strong hydrogen bonds, causing the hard segment regions to aggregate and imparting rigidity, hardness, and strength to the material. The soft segments are typically composed of long-chain polyethers or polyester polyols, with flexible molecular chains, imparting elasticity and flexibility to the material.
[0032] The modified nano-silica was purchased from Hangzhou Jiupeng New Materials, model number CY-SP30H, with a particle size of 20-30nm and a basic structural unit of [silicon-oxygen tetrahedron (SiO4)].
[0033] The thickener was purchased from Liaoning Hengxing Chemical Co., Ltd., and its model is FS-20A.
[0034] The dispersant was purchased from Liaoning Hengxing Chemical Co., Ltd., and its model was FS-5040.
[0035] The crosslinking agent was purchased from Liaoning Hengxing Chemical Co., Ltd., and its model was DF-810.
[0036] The wetting agent was purchased from Liaoning Hengxing Chemical Co., Ltd., and its model number is 8502C.
[0037] The 70D nylon four-way stretch fabric is composed of 85% N and 15% SP, with specifications of 70d+40d*70d+40d / 144*104. It was purchased from Chuanzheng Textile. The fabric used in the example is 5 meters in size.
[0038] The highly elastic and breathable nanofiber membrane was purchased from Qingdao Shengyaqi, model S2A, with a fiber diameter of 100-300 nm, an average pore size of 0.1-0.5 μm, a porosity of 82%-90%, and a moisture permeability of 10000 g / m³. 2 • 24 h or more, elastic properties: maximum elongation ratio 200%-300%.
[0039] The specific steps for the fluorine-free waterproof finishing of the fabric are as follows: 4 wt% waterproofing agent FD-8 + 0.3 wt% crosslinking agent 891A, with water added to 100 wt%. The fabric is then dried in an oven at 160℃ for 2 minutes after two dips and two nips.
[0040] Example 1
[0041] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m 2 .
[0042] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0043] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0044] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 8 g / m. 2Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0045] (5) Preparation of rubber compound, raw material weight ratio:
[0046] 20 parts of waterborne polyurethane emulsion;
[0047] Two parts of modified nano-silica;
[0048] Thickener FS-20A 2 parts;
[0049] Dispersant 906S 0.5 parts;
[0050] Crosslinking agent DF-810 1 part;
[0051] 1 part of wetting agent 8502C;
[0052] Add water to make 100 parts.
[0053] First, add the dispersant to the water and stir at a low speed of 500 rpm to dissolve it. Then, under high speed of 1200 rpm shearing, slowly add the modified nano-silica in batches until it is evenly dispersed. Mix the dispersed silica with the water-based polyurethane emulsion and stir evenly. Then, add the wetting agent and stir evenly at a low speed of 500 rpm. Finally, under continuous low speed of 500 rpm stirring, slowly add the thickener in small amounts and multiple times to achieve the target viscosity of 2500 cps, and obtain a uniform roller printing paste.
[0054] (6) The abrasion-resistant slurry obtained in (5) is applied to the surface of the composite fabric (4) by roller printing, dried at 150°C for 2 min, and the dry weight gain is 4 g / m². 2 .
[0055] Example 2
[0056] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m 2 .
[0057] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0058] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0059] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 10 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0060] (5) Preparation of rubber compound, raw material weight ratio:
[0061] 25 parts of waterborne polyurethane emulsion;
[0062] 3 parts of modified nano-silica;
[0063] Thickener FS-20A 2.2 parts;
[0064] Dispersant 5040 0.7 parts;
[0065] Crosslinking agent DF-810 1.2 parts;
[0066] Wetting agent 8502C 1.2 parts;
[0067] Add water to make 100 parts.
[0068] First, add the dispersant to the water and stir at a low speed of 500 rpm to dissolve it. Then, under high speed of 1200 rpm shearing, slowly add the modified nano-silica in batches until it is evenly dispersed. Mix the dispersed silica with the water-based polyurethane emulsion and stir evenly. Then, add the wetting agent and stir evenly at a low speed of 500 rpm. Finally, under continuous low speed of 500 rpm stirring, slowly add the thickener in small amounts and multiple times to achieve the target viscosity of 2500 cps, and obtain a uniform roller printing paste.
[0069] (6) Apply the abrasion-resistant slurry obtained in (5) to the laminated fabric (4) film surface by roller printing, dry at 150℃ for 2 min, and the dry weight gain is 6 g / m. 2 .
[0070] Example 3
[0071] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m 2 .
[0072] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0073] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0074] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 12 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0075] (5) Preparation of rubber compound, raw material weight ratio:
[0076] 25 parts of waterborne polyurethane emulsion;
[0077] 3.5 parts of modified nano-silica;
[0078] Thickener FS-20A 2.5 parts;
[0079] Dispersant 5040 0.9 parts;
[0080] Crosslinking agent DF-810 1.4 parts;
[0081] Wetting agent 8502C 1.4 parts;
[0082] Add water to make 100 parts.
[0083] First, add the dispersant to the water and stir at a low speed of 500 rpm to dissolve it. Then, under high speed of 1200 rpm shearing, slowly add the modified nano-silica in batches until it is evenly dispersed. Mix the dispersed silica with the water-based polyurethane emulsion and stir evenly. Then, add the wetting agent and stir evenly at a low speed of 500 rpm. Finally, under continuous low speed of 500 rpm stirring, slowly add the thickener in small amounts and multiple times to achieve the target viscosity of 2500 cps, and obtain a uniform roller printing paste.
[0084] (6) Apply the abrasion-resistant slurry obtained in (5) to the laminated fabric (4) film surface by roller printing, dry at 150℃ for 2 min, and the dry weight gain is 8 g / m². 2 .
[0085] Example 4
[0086] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m 2 .
[0087] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0088] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0089] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 12 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0090] (5) Preparation of rubber compound, raw material weight ratio:
[0091] 30 parts of waterborne polyurethane emulsion;
[0092] 3.5 parts of modified nano-silica;
[0093] Thickener FS-20A 2.5 parts;
[0094] Dispersant 5040 1.0 part;
[0095] Crosslinking agent DF-810 1.5 parts;
[0096] 1.5 parts of wetting agent 8502C;
[0097] Add water to make 100 parts.
[0098] First, add the dispersant to the water and stir at a low speed of 500 rpm to dissolve it. Then, under high speed of 1200 rpm shearing, slowly add the modified nano-silica in batches until it is evenly dispersed. Mix the dispersed silica with the water-based polyurethane emulsion and stir evenly. Then, add the wetting agent and stir evenly at a low speed of 500 rpm. Finally, under continuous low speed of 500 rpm stirring, slowly add the thickener in small amounts and multiple times to achieve the target viscosity of 2500 cps, and obtain a uniform roller printing paste.
[0099] (6) Apply the abrasion-resistant slurry obtained in (5) to the composite fabric (4) film surface by roller printing, dry at 150℃ for 2 min, and the dry weight gain is 10 g / m. 2 .
[0100] Example 5
[0101] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m 2 .
[0102] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0103] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0104] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 12 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0105] (5) Preparation of rubber compound, raw material weight ratio:
[0106] 35 parts of waterborne polyurethane emulsion;
[0107] 4 parts of modified nano-silica;
[0108] Thickener FS-20A 2.5 parts;
[0109] Dispersant 5040, 1.2 parts;
[0110] Crosslinking agent DF-810 1.8 parts;
[0111] Wetting agent 8502C 1.8 parts;
[0112] Add water to make 100 parts.
[0113] First, add the dispersant to the water and stir at a low speed of 500 rpm to dissolve it. Then, under high speed of 1200 rpm shearing, slowly add the modified nano-silica in batches until it is evenly dispersed. Mix the dispersed silica with the water-based polyurethane emulsion and stir evenly. Then, add the wetting agent and stir evenly at a low speed of 500 rpm. Finally, under continuous low speed of 500 rpm stirring, slowly add the thickener in small amounts and multiple times to achieve the target viscosity of 2500 cps, and obtain a uniform roller printing paste.
[0114] (6) Apply the abrasion-resistant slurry obtained in (5) to the laminated fabric (4) using a roller printing method, dry at 150℃ for 2 min, and the dry weight gain is 12 g / m. 2 .
[0115] Example 6
[0116] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m 2 .
[0117] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0118] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0119] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 12 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0120] (5) Preparation of rubber compound, raw material weight ratio:
[0121] 35 parts of waterborne polyurethane emulsion;
[0122] 5 parts of modified nano-silica;
[0123] Thickener FS-20A 2.5 parts;
[0124] Dispersant 5040, 1.2 parts;
[0125] Crosslinking agent DF-810, 2.0 parts;
[0126] Wetting agent 8502C 2.0 parts;
[0127] Add water to make 100 parts.
[0128] First, add the dispersant to the water and stir at a low speed of 500 rpm to dissolve it. Then, under high speed of 1200 rpm shearing, slowly add the modified nano-silica in batches until it is evenly dispersed. Mix the dispersed silica with the water-based polyurethane emulsion and stir evenly. Then, add the wetting agent and stir evenly at a low speed of 500 rpm. Finally, under continuous low speed of 500 rpm stirring, slowly add the thickener in small amounts and multiple times to achieve the target viscosity of 2500 cps, and obtain a uniform roller printing paste.
[0129] (6) Apply the abrasion-resistant slurry obtained in (5) to the laminated fabric (4) film surface by roller printing, dry at 150℃ for 2 min, and the dry weight gain is 14 g / m. 2 .
[0130] Example 7
[0131] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m 2 .
[0132] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0133] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0134] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 12 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0135] (5) Preparation of rubber compound, raw material weight ratio:
[0136] 40 parts of waterborne polyurethane emulsion;
[0137] 6 parts of modified nano-silica;
[0138] Thickener FS-20A 2.5 parts;
[0139] Dispersant 5040, 1.5 parts;
[0140] Crosslinking agent DF-810, 2.0 parts;
[0141] Wetting agent 8502C 2.0 parts;
[0142] Add water to make 100 parts.
[0143] First, add the dispersant to the water and stir at a low speed of 500 rpm to dissolve it. Then, under high speed of 1200 rpm shearing, slowly add the modified nano-silica in batches until it is evenly dispersed. Mix the dispersed silica with the water-based polyurethane emulsion and stir evenly. Then, add the wetting agent and stir evenly at a low speed of 500 rpm. Finally, under continuous low speed of 500 rpm stirring, slowly add the thickener in small amounts and multiple times to achieve the target viscosity of 2500 cps, and obtain a uniform roller printing paste.
[0144] (6) Apply the abrasion-resistant slurry obtained in (5) to the composite fabric (4) film surface by roller printing, dry at 150℃ for 2 min, and the dry weight gain is 16 g / m. 2 .
[0145] The unmodified nanofiber membrane mentioned in the technical background is composited with the fabric, and the technical indicators of the product in the experimental embodiment of the present invention are compared with those of the present invention.
[0146] Comparative Example 1
[0147] (1) Fabric selection: 30D, 375T plaid spring spun fabric, weight 60 g / m 2 .
[0148] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0149] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0150] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 12 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0151] Comparative Example 2
[0152] (1) Fabric selection: 70D nylon four-way stretch, weight 125 g / m2 .
[0153] (2) The membrane material is a high-elasticity and breathable nanofiber membrane (thickness 15 μm, basis weight 9 g / m³). 2 )S2A.
[0154] (3) The fabric is treated with fluorine-free waterproofing, with a water repellency rating of ≥4.
[0155] (4) The water-repellent treated fabric and (2) nanofiber membrane are bonded together on a laminating machine using adhesive dots. The bonding agent is an environmentally friendly reactive polyurethane hot melt adhesive, the operating temperature is 95℃, and the amount of adhesive applied is 12 g / m. 2 Curing time is 2 days (48 hours) in an environment with a temperature of 25°C and a humidity of over 50%.
[0156] The products prepared in Examples 1-7, Comparative Examples 1 and 2 were subjected to performance tests. The specific technical comparison results are shown in Table 1 below.
[0157] The testing method is as follows:
[0158] Fabric abrasion test Martindale method: The degree of abrasion is tested and evaluated according to GB / T 21196.4 standard;
[0159] Gram weight test: Tested according to GB / T 4669 standard;
[0160] Moisture permeability test: Tested according to GB / T 12704.2.B standard;
[0161] Hydrostatic pressure test to determine water resistance: Tested according to GB / T 4744 standard;
[0162] Wash resistance test: Wash 5 times according to GB / T 8629 4N procedure;
[0163] Air permeability test: according to GB / T 5453 (pressure 100Pa, area 20 cm²) 2 ).
[0164] Table 1 Test Results
[0165]
[0166] As can be seen from the table above:
[0167] 1. Abrasion resistance (in cycles, higher values indicate greater abrasion resistance)
[0168] Examples 1-6 show a steady increase in the number of wear-resistant cycles:
[0169] The wear resistance was continuously optimized from 12050 to 12500, from 13000 to 13500, from 14000 to 15000 cycles; in Example 7, the wear resistance dropped slightly to 14000 cycles.
[0170] This demonstrates that adjusting the gradient of the formulation components can continuously improve the wear resistance and scratch resistance of the film. Example 6 achieved the peak wear resistance in this group, demonstrating the best wear resistance and durability.
[0171] 2. Hydrostatic pressure (kPa, the higher the value, the stronger the waterproof barrier)
[0172] The overall trend from Example 1 (80 kPa) to Example 7 (88 kPa) is continuously upward, gradually improving the initial waterproof performance of the fabric; Example 6 has a hydrostatic pressure of 85 kPa, which takes into account both waterproof and other breathable and moisture-wicking indicators, without sacrificing comfort due to excessive waterproofing.
[0173] 3. Water pressure after 5 washes (a core indicator of water resistance and durability; the higher the pressure, the better the water resistance and durability).
[0174] In Examples 1-6, the water pressure increased significantly after washing: 35→35→37→38→45→48 kPa, and the water retention rate was significantly improved after washing; in Example 7, the pressure dropped back to 45 kPa.
[0175] Example 6 shows that the coating has the best adhesion and the least water resistance loss after repeated washing. The garment can still maintain excellent water resistance after multiple washes, which is a key advantage of the garment fabric.
[0176] 4. Moisture permeability (g / m 2 • 24 hours, the higher the breathability and sweat-wicking capacity, the better.
[0177] Examples 1-6 show a gradual decrease in moisture permeability:
[0178] 7000→6900→6950→6850→6850→6830 g / m 2 • Over 24 hours, as abrasion resistance and waterproof performance improve, moisture permeability decreases slightly, but the decrease is minimal.
[0179] In Example 7, the moisture permeability increased to 6800, slightly lower than in Example 6.
[0180] This indicates that while significantly enhancing abrasion resistance and waterproofing, the formula system only slightly sacrifices breathability, maintaining a high level of breathability and balancing waterproofing with comfortable wear.
[0181] 5. Weight (g / m³) 2 )
[0182] Examples 1-7 show a continuous linear increase in weight: 151 → 163 g / m³ 2As the coating amount increases with the formula gradient, the fabric thickness increases, and the wear resistance and waterproof performance are simultaneously enhanced; Example 6: 161 g / m² 2 It balances weight and full functionality without being too heavy and increasing the burden of wearing it.
[0183] 6. Breathability (mm / s, the higher the value, the better the air permeability)
[0184] In Examples 1-7, the air permeability decreased continuously: 2.5 → 2.0 mm / s. The increase in membrane thickness and density slightly reduced the air permeability. In Example 6, the air permeability was 2.3 mm / s, which still maintained a qualified air permeability level and did not show a significant deterioration in air permeability.
[0185] 7. Fastness after 10 washes
[0186] Examples 1-7 showed no peeling after 10 washes, all coatings met the adhesion standards, and all formulations met the basic requirements for wash fastness of garments with no significant differences.
[0187] From Examples 1 to 6, with the gradual adjustment of the formula ratio, the three core protective properties of the fabric—abrasion resistance, hydrostatic pressure, and water-washable durability—continue to improve, while moisture permeability and breathability only slightly decrease, and the weight increases slightly and controllably, resulting in balanced optimization of all indicators. In Example 7, the two core waterproof and abrasion resistance indicators—abrasion resistance and water-washable pressure—decline, and the overall performance is weaker than that of Example 6.
[0188] A horizontal comparison of Examples 1 to 7 shows that Example 6 is the optimal formulation, which maximizes the abrasion resistance, washability and waterproof performance of the coating while retaining excellent moisture permeability and breathability, perfectly balancing the protective function and wearing comfort of the garment.
[0189] In contrast, Comparative examples 1 and 2 only possess basic advantages such as lightness, thinness, and high breathability and moisture permeability, but their abrasion resistance is extremely poor, and their waterproof performance drops drastically after washing, failing to meet the long-term waterproof and abrasion-resistant functional clothing requirements.
[0190] Example 6 achieves a significant improvement in abrasion resistance, washability, and waterproof performance with only a slight sacrifice in breathability and moisture permeability. It balances the fabric's protective durability with everyday wearing comfort, perfectly solving the industry shortcomings of traditional waterproof fabrics such as poor abrasion resistance and washing failure. It is the roller printing and lamination formula solution with the best overall performance.
[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A wear-resistant nanofiber membrane composite fabric, characterized in that, The material includes a base fabric, a nanofiber membrane bonded thereto, and a wear-resistant coating disposed on the surface of the nanofiber membrane. The wear-resistant coating is formed by roller printing and drying of a wear-resistant slurry. The raw materials of the wear-resistant slurry are formulated in the following proportions by weight: 20-40 parts of waterborne polyurethane emulsion, 2-6 parts of modified nano silica, 2-3 parts of thickener FS-20A, 0.5-1.5 parts of dispersant 5040, 1-2 parts of crosslinking agent DF-810, 1-2 parts of wetting agent 8502C, and water to make up to 100 parts.
2. The wear-resistant nanofiber membrane composite fabric according to claim 1, characterized in that, The dry weight gain of the coating is 4-16 g / m³. 2 .
3. The wear-resistant nanofiber membrane composite fabric according to claim 1, characterized in that, The base fabric is 70D nylon four-way stretch with a weight of 125 g / m². 2 .
4. The wear-resistant nanofiber membrane composite fabric according to claim 1, characterized in that, The nanofiber membrane is a highly elastic and breathable nanofiber membrane S2A, with a thickness of 15 μm and a basis weight of 9 g / m³. 2 .
5. The wear-resistant nanofiber membrane composite fabric according to claim 1, characterized in that, The aqueous polyurethane emulsion is aqueous polyurethane FS-781, and the modified nano silica is CY-SP30H.
6. The method for preparing a wear-resistant nanofiber membrane composite fabric according to claim 1, characterized in that, The steps are as follows: Step 1: The fabric base and the nanofiber membrane are laminated together on a laminating machine using hot melt adhesive to obtain the composite fabric; Step 2: Prepare abrasion-resistant slurry, wherein the abrasion-resistant slurry comprises an aqueous polyurethane emulsion, modified nano-silica, thickener, dispersant, crosslinking agent, wetting agent, and water; Step 3: Apply the abrasion-resistant slurry to the nanofiber membrane surface of the composite fabric using a roller printing method; Step 4: Dry the composite fabric with the applied abrasion-resistant slurry to form an abrasion-resistant coating on the surface of the nanofiber membrane.
7. The method for preparing a wear-resistant nanofiber membrane composite fabric according to claim 6, characterized in that, In step one, the base fabric undergoes a water-repellent treatment before lamination, with a water repellency level ≥ 4. The water-repellent treatment is as follows: 4 wt% of waterproofing agent FD-8 and 0.3 wt% of crosslinking agent 891A are mixed, and water is added to 100 wt%. The fabric is then dried in an oven at 160℃ for 2 minutes after two dips and two rubs.
8. The method for preparing a wear-resistant nanofiber membrane composite fabric according to claim 6, characterized in that, The hot melt adhesive used in step two is a reactive polyurethane hot melt adhesive, with an application rate of 8-12 g / m². 2 After lamination, the material is cured at a temperature of 25°C and a humidity of not less than 50% for 2 days.
9. The method for preparing a wear-resistant nanofiber membrane composite fabric according to claim 6, characterized in that, In step three, the preparation method of the wear-resistant slurry is as follows: First, the dispersant is added to water and dissolved under low-speed stirring at 500 rpm; then, modified nano-silica is slowly added in batches under high-speed shearing at 1200 rpm and dispersed evenly; the dispersed silica mixture is mixed and stirred evenly with the water-based polyurethane emulsion; then, the wetting agent is added and stirred evenly at low speed at 500 rpm; finally, the thickener is slowly added under continuous low-speed stirring at 500 rpm to adjust to the target viscosity of 2500 cps.
10. The method for preparing a wear-resistant nanofiber membrane composite fabric according to claim 6, characterized in that, In step four, the drying process is as follows: drying at 150-160℃ for 2 minutes.